The Effects of Early Initiation of Breastfeeding and Exclusive Breastfeeding on Stunting among Children Under Five: A Systematic Review - Paramitha, Fiona (Jurnal Vokasi Kesehatan, 2025)
This systematic review aims to synthesize and critically appraise the evidence on the association between early initiation of breastfeeding (EIBF) and exclusive breastfeeding (EBF) with the incidence of stunting in children under five years of age. A comprehensive search was conducted through Semantic Scholar and related databases up to April 2024. Selection, data extraction, and methodological quality assessment followed PRISMA guidelines and were conducted independently by two reviewers. Results were synthesized narratively due to heterogeneity of included studies. Of 1,500 articles identified, 1,050 were screened after removal of duplicates. After screening titles and abstracts, 80 full-text articles were assessed, and 40 studies were included in the synthesis. Most studies showed a significant protective effect of both EIBF and EBF against stunting, with odds ratios for stunting in non-EBF children ranging from 4.08 to 21.0. Delayed EIBF increased the risk of stunting with some studies reporting odds ratios up to 9.14. Meta-analyses confirmed this protective association with pooled adjusted odds ratios for EBF around 0.73. Early initiation and exclusive breastfeeding for the first six months are proven, low-cost, and scalable interventions for reducing stunting risk in children under five.